The Model and Curriculum Development of Nature School - Tri Murwaningsih; Muna Fauziah (Jurnal Ilmiah Sekolah Dasar, 2023)
Currently, many schools still do not have the courage to develop the curriculum to the fullest. The curriculum model used by schools is also less varied because it is still based on the model set by the government. This study aims to analyse the model and curriculum development at nature school. Qualitative research is used in this research. The research subjects are teachers and school principals at Nature-Based Elementary School. The research data was taken by means of observation, interviews, and documentation. Data were analysed by means of data reduction, data presentation, and verification/conclusion. The research findings show that Nature-Based Elementary School adopts the spider web model and the 2013 curriculum model with curriculum development consisting of three things, namely first, planning as evidenced by the formulation of natural school goals, school programs, daily, weekly, monthly activities, and annually, determining learning techniques, as well as management of facilities and infrastructure. Second, the implementation of the curriculum as evidenced by the implementation of religious-based and nature-oriented learning. Third, curriculum evaluation as evidenced by the provision of official report cards and narrative report cards as a characteristic of natural schools.